Information Technology in the Human Services : Dreams and Realities : Husita 4 - Kemppainen, Erkki; Vaarama, Marja; Ekberg, Jan; Routio, Ritva; Salminen, Anna-Liisa (Stakes, 1996)
Human Services Information Technology Applications (HUSITA) : Fourth International Conference and Exhibition